KEANEKARAGAMAN JENIS IKAN DIPERAIRAN SUNGAI CASANOVA DESA NAMU SURO KECAMATAN BIRU-BIRU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Benny Arianta; Eri Yusni; Zulham Apandy Harahap (AQUACOASTMARINE, 2018)
The research has been conducted in the Casanova River, on Biru-biru District, Deli Serdang Region, of North Sumatera. This research wash done by purposive sampling method and three different stations based on community activity, Sampling of This research consists of two ordos, two families, four genera and four spesies. The species obtained are Oreochromis niloticus, Hampala macrolepidota, Mystacoleucus marginatus, Barbodes schwanenfelldi. Based on the value of K (density), KR (relative density), and FK (frequency of attendance) at Station I, II, and III, the highest value was found at station I of 0,04 ind / m2, 77,42%, 0,77% with species of Oreochromis niloticus. Compared the other species was lowers index dominance at 0.92 ind / m2, and the uniformity index was found at 1,46 ind / m2. However index for all station was found Oreochromis niloticus higher at 68,51 %.Keywords: Fish, Diversity, Casanova River, Deli Serdang, Sumatera Utara.